2009
DOI: 10.1016/j.devcel.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Vascular Integrity by Endothelial Cell Junctions: Molecular Basis and Pathological Implications

Abstract: Human pathologies such as vascular malformations, hemorrhagic stroke, and edema have been associated with defects in the organization of endothelial cell junctions. Understanding the molecular basis of these diseases requires different integrated approaches which include basic cell biology, clinical studies, and studies in animal models such as mice and zebrafish. In this review we discuss recent findings derived from these approaches and their possible integration in a common picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
644
1
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(670 citation statements)
references
References 107 publications
13
644
1
12
Order By: Relevance
“…Adherens junctions are of importance for regulation of vascular permeability and conditions that cause increased vascular permeability often alter their structural features [4]. A key player in regulation of these events is the cell adhesion protein VE-cadherin [5] and VEGF-A is thought to via its receptor VEGFR-2 affect the localization and functional characteristics of VE-cadherin [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherens junctions are of importance for regulation of vascular permeability and conditions that cause increased vascular permeability often alter their structural features [4]. A key player in regulation of these events is the cell adhesion protein VE-cadherin [5] and VEGF-A is thought to via its receptor VEGFR-2 affect the localization and functional characteristics of VE-cadherin [3].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-induced vascular permeability is thought to result from either transport through vesiculo-vacuolar organelles [2] or a VEGFR-2 dependent dissociation of adherens junctions [3]. The cell-cell interacting molecule VE-cadherin is the primary organizer of adherens junctions [4,5] and VEGF-A causes its dissociation from this site [6]. VE-cadherin and VEGFR-2 have been found to be in complex with each other [5] but how VEGF-A dissociates VE-cadherin from adherens junctions remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…NO mediates disruption of endothelial AJ, which comprise VE-cadherin and intracellular associated proteins including β-catenin and p120 catenin, 12 and increases vascular permeability. 22,23,25 Recent studies 31,34 demonstrated that VEGF stimulation of eNOS induced S-nitrosylation of β-catenin, leading to disassembly of AJ complexes.…”
Section: S-nitrosylation Of β-Cateninmentioning
confidence: 99%
“…11 Platelet-activating factor (PAF), histamine and leukotrienes are edematogenic mediators that disrupt vascular barrier integrity, which is sustained mainly by the endothelial adherens junction (AJ) comprising VE-cadherin and its associated proteins. 12 In anaphylaxis, these edematogenic mediators are released mainly from mast cells through antigen engagement of mast cell-associated IgE and act on vascular endothelium and smooth muscle to cause severe vascular leakage and hypotension. 13 To establish novel therapies for anaphylaxis, it is important to better understand the pathophysiological mechanisms underlying vascular barrier disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells express cell-type-specific tyrosine kinase receptors, including vascular endothelial growth factor, Tie, and Eph receptors [41,42], while alveolar epithelial cells also express specific molecules [43]. A549 cells are type 2 alveolar cells and synthesize surfactant proteins [44].…”
Section: Discussionmentioning
confidence: 99%